Increasing Student Activity and Learning Outcomes in Online Learning at SMPN 10 Serang City - Sulasiah, Yayah (LPPM Universitas Primagraha, 2022)
The purpose of this study was to increase the activity and learning outcomes of Civics through the learning method of Giving Assignments with Video Media for Class IX A students of SMPN 10 Serang City. This research is classroom action research, and the hypothesis in this study is that activeness and learning outcomes can be increased by using the Assignment Method with Video Media. The subject who took the action was the teacher (researcher) with the Civics subject teacher as an observer). The results of the study showed that using the Assignment Using Video Media method turned out to be more effective in the learning process, as indicated by increased activity and student learning outcomes: 1) . The application of learning assignments with video media can increase student activity in Civics lessons, namely in the Pre-Cycle 57.84%, Cycle I 67.88%, Cycle II 75.68% of the total 34 students. 2). Student learning outcomes increased as indicated by an increase in the average student pre-cycle (56.6) or 38% of students completed, Cycle I averaged (70.85) or 73% and in Cycle II the average increased to (75, 29) or 94%. Based on the results of this study it can be concluded that learning Citizenship Education using the Assignment Learning method with Video Media is more likely to increase student activity and learning outcomes when compared to learning using the lecture method